2015
DOI: 10.1002/cam4.461
|View full text |Cite
|
Sign up to set email alerts
|

Meat intake, cooking methods, dietary carcinogens, and colorectal cancer risk: findings from the Colorectal Cancer Family Registry

Abstract: Diets high in red meat and processed meats are established colorectal cancer (CRC) risk factors. However, it is still not well understood what explains this association. We conducted comprehensive analyses of CRC risk and red meat and poultry intakes, taking into account cooking methods, level of doneness, estimated intakes of heterocyclic amines (HCAs) that accumulate during meat cooking, tumor location, and tumor mismatch repair proficiency (MMR) status. We analyzed food frequency and portion size data inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 45 publications
3
41
0
4
Order By: Relevance
“…Although the most common HCAs found in human diets have been shown to be carcinogenic in rodents (Shirai et al, 1995; Ito et al, 1997), epidemiologic studies have produced inconsistent data regarding associations of HCAs with human cancer (Augustsson et al, 1999; Joshi et al, 2015). In fact, while many authors have found a positive association between HCA’s and breast, prostate, lung, and renal cancer (Ferrucci et al, 2009; Cross et al, 2005; Tasevska et al, 2009; Daniel et al, 2012), a recent prospective analysis revealed that intake of these meat-derived mutagens was not significantly associated with colorectal cancer risk (Le et al, 2016).…”
Section: Existing Theories To Explain Increased Disease Risks Of Rmentioning
confidence: 99%
“…Although the most common HCAs found in human diets have been shown to be carcinogenic in rodents (Shirai et al, 1995; Ito et al, 1997), epidemiologic studies have produced inconsistent data regarding associations of HCAs with human cancer (Augustsson et al, 1999; Joshi et al, 2015). In fact, while many authors have found a positive association between HCA’s and breast, prostate, lung, and renal cancer (Ferrucci et al, 2009; Cross et al, 2005; Tasevska et al, 2009; Daniel et al, 2012), a recent prospective analysis revealed that intake of these meat-derived mutagens was not significantly associated with colorectal cancer risk (Le et al, 2016).…”
Section: Existing Theories To Explain Increased Disease Risks Of Rmentioning
confidence: 99%
“…However, there are still debates on the potential relationship between red meat consumption and CRC [20,21] . Though some studies found no association between red or unprocessed meat and CRC, high processed meat intake was related with an increased risk of CRC, especially distal colon cancer [21,22] .…”
Section: Red or Processed Meatmentioning
confidence: 99%
“…One article was subsequently excluded because it did not met the inclusion criteria since estimated the exposure to HCAs (low, intermediate and high) on the base of red meat source and preparation but not give their concentrations. Therefore, at the end of the selection process, 39 studies which met the inclusion criteria were enclosed in the systematic review and meta-analysis (Figure 1), 17 on CRA [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46], 20 on CRC [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][66], and 2 studies reported data on both CRA and CRC [67,68]. …”
Section: Resultsmentioning
confidence: 99%
“…Case-control studies were published between 1997 and 2015, 16 were population-based [48-57,62-65,67,68], 2 were hospital-based [47,58] and one was cohort-based [57]. Eighteen studies were conducted in the United States [49][50][51][52][53][54][55][56][57][59][60][61][62][63][64][66][67][68] and one each in Uruguay [47], Europe [48], Japan [58] and Canada [65]. Cohort studies were published between 2010 and 2016, all of them were conducted in the United States [60,61,66].…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
See 1 more Smart Citation